Analysis of the effect of rolling speed on the texture properties of noodle dough from water-solid interaction, development of gluten network, and bubble distribution. (15th March 2023) - Liu, Shuyi; Jiang, Yiyi; Xu, Bin; Jiang, Song
Highlights: As rolling speed increased, the tensile force and hardness of dough sheet decreased. Increasing the rolling speed increased water mobility and weakened gluten network. The gluten network and texture of the dough sheet in length direction was more responsive to the change in rolling speed. In thickness direction, bubbles number decreased, from the center part to the edge. At lower rolling speed, fewer bubbles led to higher tensile force and hardness. Abstract: To explore the influence of rolling speed on texture property of the noodle dough with 34% and 38% water additions, the water status, development of gluten network, and bubble distribution were studied. The dough sheets with 38% water addition had more uniform gluten network, and fewer bubbles, but lower hardness and tensile force because of the softening effect of water. As rolling speed increased, the water mobility increased, gluten network became weakened, and bubble number increased, leading to decreases in texture properties. Dough sheets with 38% water addition were less responsive to changes in rolling speed than that with 34% water addition because of the higher hydration of gluten. With increasing rolling speed, the total length and number of gluten network lines in length direction (rolling direction) reduced more than those in width direction, corresponding to the greater reductions in the texture properties of the dough sheet in length direction.